2010
DOI: 10.2214/ajr.10.4600
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Imaging-Guided Biopsy as an Adjuvant to Minimally Invasive Autopsy With CT and Postmortem Angiography: A Feasibility Study

Abstract: In light of increasing objections of the next of kin toward an autopsy and the necessity for medical examiners to assess the manner and cause of death, we think that the minimally invasive procedure described here may present a viable compromise in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 17 publications
1
39
0
8
Order By: Relevance
“…However, when there are no fatal findings or only non-specific findings on MDCT, postmortem MRI will be a useful option for postmortem evaluation. Recently, minimally invasive imaging techniques, such as postmortem angiography and postmortem biopsy, have been developed [6,18,20,22]. Postmortem CT angiography is able to provide information about the vascular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when there are no fatal findings or only non-specific findings on MDCT, postmortem MRI will be a useful option for postmortem evaluation. Recently, minimally invasive imaging techniques, such as postmortem angiography and postmortem biopsy, have been developed [6,18,20,22]. Postmortem CT angiography is able to provide information about the vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Because of advances in medical imaging technologies, postmortem multidetector computed tomography (MDCT) and magnetic resonance imaging (MRI) have been introduced into forensic examination [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Some investigators have reported the utility of postmortem imaging for traumatic deaths.…”
Section: Introductionmentioning
confidence: 99%
“…R. Soc. B 370: 20140253 be taken and examined histologically [26]. Also, tissue and fluid samples can be collected for toxicological and microbiological examinations.…”
Section: (B) Magnetic Resonance Imagingmentioning
confidence: 99%
“…Imaging cannot compete with the external examination of a body [11], and although this can be performed by imaging [12] it rarely needs to outside specific circumstances. Furthermore toxicology and even histology via targeted biopsy can be routinely added to an imaging examination [13,14].…”
Section: Contextmentioning
confidence: 99%